APLIKASI PEMBELAJARAN ARITMETIKA MENGGUNAKAN METODE BACKUS NAUR FORM (BNF) BERBASIS ANDROID DI SDN RAMPAL CELAKET MALANG - Prayoga Wahyu Setiawan; Dwi Safiroh Utsalina (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2025)
The user growth of tablets and smartphones among students in Indonesia can be used as an opportunity to help increase interest in learning and understanding a lesson for students.From the results of observations made in SDN Rampal Celaket Malang, Arithmetic subchapter of Mathematics is one of the difficult subject matter to be understood by students and elementary school grades 1 to 3. that's why proposed to construct an learning arithmetic applications based on Android.